ANALISIS ANGKA KONVERSI PENGUKURAN KAYU BULAT DI AIR UNTUK JENIS MERANTI (Shorea spp) - Budiyana, .; Dewantara, Iswan; Yani, Ahmad (JURNAL HUTAN LESTARI, 2018)
The determination of the conversion rate (1.04) for certain types of wood still contains weaknesses, this is caused by bontos diverse forms. Where the measurement results will be very different for logs that have bontos cylindrical shape with a cylindrical timber that is not or has buttresses. It is necessary for research that aims to determine how much the conversion rate measurement volume of logs in the water compared to the measurement volume of logs on land for Meranti (Shorea spp). Logs were observed and measured the average diameter of at least / lowest is 60 cm by 50 stems. Implementation of measurement include: measuring the length of logs on land and in water, measuring the diameter of logs on land and in water as well as the determination of the volume of logs on land and in water. From the results of statistical analysis using the t test in one direction, the result is greater than the figure of 2.17 t tables for 5% significance level = 1.67 and smaller for a very real level of 1% is 2.40, which means that Ho is rejected on the the real rate of 5%, which means that the diameter measurements on land and in water / river for Meranti (Shorea spp) influence the treatment of the measurement method because it produces a real difference.Keyword : Conversion Rate, Grading, Log, Shorea spp